PENINGKATAN HASIL BELAJAR IPA MELALUI IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING - sriani . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research was carried out aimed at improving student learning outcomes in science subjects in terms of the characteristics of living things through the use of Discovery Learning Learning Model in class VI-A of SD Negeri 1 Peureulaksemen I in 2017-2018 Academic Year. The benefits of this research are to add new references and theories in the field of education, especially in the implementation of Classroom Action Research by applying various models or learning methods so as to improve student learning outcomes. To achieve this, the step that needs to be implemented is to use the Discovery Learning Learning Model. Data analysis method used in this study uses descriptive analysis whose data is sourced from formative tests and classroom observations. This research was conducted in two cycles, each cycle consisting of two meetings. The expected indicator of success in this study is the increase in students' mastery learning which reaches 85% classically. The results showed, in cycle I (one) the average value of students amounted to 71.25 and mastery learning reached 58.33%. These results indicate an increase from the initial conditions with an average score of only 59.79 and a new learning completeness of 33.33%. While in cycle II (two) the average value of students is 79.58 and the learning completeness reaches 95.83%. The conclusion of this study is the use of the Discovery Learning Model in the learning of IPA material characteristics of living things can have a positive effect on improving student learning outcomes in class VI-A SD Negeri 1 Peureul Semester I 2017-2018 Academic Year.